Antioxidant properties of soft coral Dendronephthya sp - Saad, Shahbudin; Darnis, Deny Susanti; Tengku Abdul Hamid , Tengku Haziyamin; John, Akbar; Bakhtiar, M. Taher (A N S I Network, 2011)
Present study was conducted to determine the antioxidant property of soft corals belong to the genus: Dendronephthya (Family: Nephtheidae) using α, α-Diphenyl-β-PicrylHydrazyl (DPPH) radical-scavenging and Ferric Thiocyanate (FTC) methods using vitamin E as a positive control. Crude extracts were prepared from 4 Dendronephthya sp. using aqueous, dichoromethane: methanol and methanol extraction. All crude extracts of Dendronephthya sp. exhibited antioxidant properties and the white spots appeared during the rapid screening using Dot-Blot and 1, 1-Diphenyl-2-picryl-hydrazyl (DPPH) staining where the concentration of crude extract was 1.00 g mL-1 against the DPPH concentration of 0.4 mM. In DPPH assay, not all crude extracts showed a significant value in antioxidant activities thus it could be considered as weak free radical species scavenger. The crude extract were diluted to 1000, 500, 250, 125, 63, 31, 15, 7, 4 and 2 μg mL-1, respectively and tested against highly diluted DPPH (0.06 mM). The IC50 for all crude extracts were greater than 1000 μg mL-1. The percentage of free radical scavenging exhibited by the crude extract was at 2 μg mL-1 concentration (the lowest concentration in serial dilution) with 0.81 to 2.89%. Ferric Thiocyanate (FTC) assay, showed absorbance ranges for control, vitamin E and sample were recorded as 0.012-0.858, 0.001-0.315 and 0.001-0.886, respectively. Inhibition percentage of all the crude extract was closer to the control indicated that they are weak lipid peroxidation inhibitor. However, the aqueous extract of species A and C showed higher inhibition percentage from other extract with the percentage value of 10.8 and 10.5% , respectively.